Inferences on gynoecium evolution in Xyris (Xyridaceae, Poales) based on floral anatomy and development - Nardi, Kaire De Oliveira [UNESP]; Campbell, Lisa M; Oriani, Aline [UNESP] (Oxford University Press (OUP), 2021)
The floral anatomy and development of species belonging to all sections of Xyris (Xyris, Nematopus and Pomatoxyris) were investigated comparatively to elucidate gynoecium evolution in the genus, because placentation has been one of the key characters in recognizing its taxonomic sections. In species of section Pomatoxyris (axile placentation), the tricarpellate syncarpous ovary consists of a fertile synascidiate zone, whereas the symplicate zone is fertile only in its lower portion. In species of section Xyris (parietal placentation), the ovary has a short almost sterile synascidiate zone, whereas the more extensive symplicate zone is fertile. In species of section Nematopus (free-central or basal placentation), there is an extremely short and sterile trilocular, completely septate zone at the ovary base. Such differences are related to different patterns of gynoecium development. The ancestral character state reconstruction of placentation types shows that axile placentation is the most likely ancestral condition in Xyris, from which parietal and free-central placentation were derived by shortening of the septa during the evolution of the genus. Basal placentation evolved from free-central placentation and appeared independently several times in section Nematopus. Because the phylogenetic position of X. ptariana and X. teinosperma (section Nematopus) is unknown, either the axile placentation in these species is a reversal or highlights the need for a revised infrageneric classification.
Keywords: floral organogenesis; floral vasculature; gynoecium development; ovary structure; placentation